Promotion Strategy and Customer Satisfaction on Student Enrollment Rate: Mediating Role of Value Co-Creation at an Islamic Boarding School Indonesia - Abdul Azis; Yudha Budi Abadi; Zulkifli Sultan (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to analyze the effect of promotion strategy and customer satisfaction on student enrollment rates, with value co-creation as a mediating variable, in the context of Islamic boarding schools (pesantren) in Indonesia. This research is motivated by the phenomenon of stagnation in new student growth occurring in several pesantren despite continuous promotional efforts. The Service-Dominant Logic (SDL) approach is employed to explain the role of interaction and collaboration between educational institutions and parents in the process of educational value creation. Methodology: This study employs a quantitative approach with a cross-sectional survey design. Data were collected from parents or guardians of junior and senior high school students at Pesantren Ibnu Salam Nurul Fikri, Serang. A total of 147 samples were obtained, and data were analyzed using Structural Equation Modeling based on Partial Least Squares (PLS-SEM) to examine both direct and indirect relationships among variables. Results: The results show that promotion strategy has no significant direct effect on student enrollment rates. Conversely, customer satisfaction has a positive and significant effect on student enrollment decisions. Value co-creation also proves to have a positive and significant effect on student enrollment rates. Furthermore, value co-creation fully mediates the relationship between promotion strategy and student enrollment rates, and partially mediates the relationship between customer satisfaction and student enrollment rates. Findings: The findings indicate that the simultaneous influence of promotion strategy and customer satisfaction on student enrollment rates becomes stronger when mediated by value co-creation. Novelty & Originality: The novelty of this study lies in the application of Service-Dominant Logic to the context of Islamic education marketing, an area rarely explored in prior research. Its originality emerges from the integration of value co-creation as a mediating mechanism between promotional efforts and enrollment outcomes in the pesantren setting. Conclusions: This study concludes that increasing student enrollment in pesantren cannot rely solely on promotion strategies. Pesantren need to prioritize customer satisfaction and encourage value co-creation processes through active involvement of parents and prospective students. These findings strengthen the relevance of Service-Dominant Logic in the context of Islamic education marketing and provide practical implications for managing pesantren promotion strategies. Type of Paper: This paper is an empirical research paper.